Biomedical magnesium-based composite material as well as preparation method and application thereof

By combining nanomanganese-coated microtitanium particles with magnesium-zinc-zirconium alloy powder, a biomedical magnesium-based composite material with MnZn2 phase and high-density twins is formed, which solves the problem of rapid degradation and corrosion of biomagnesium alloys in the body, significantly improves the mechanical properties and corrosion resistance of the material, extends the service life and reduces the harm to human tissues.

CN119843124AActive Publication Date: 2025-04-18GUANGDONG INST OF NEW MATERIALS

Patent Information

Application Number
CN202510315295.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The rapid degradation and corrosion of biomagnesium alloys in the body leads to a decrease in the mechanical properties and stability of the implanted material, affecting the recovery and treatment of the implanted site, and may cause potential harm to human tissues.

Method used

By combining nanomanganese coated microtitanium particles with magnesium-zinc-zirconium alloy powder in a specific proportion, a biomedical magnesium-based composite material with nanoscale MnZn2 phase and high-density nano-size twins is formed. This material reacts nanomanganese with magnesium alloy matrix to form fine MnZn2 phases and high-density twins, improving the mechanical properties and corrosion resistance of the material.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of biomedical magnesium-based composite materials, extends the service life of the implanted materials, and has an appropriate degradation rate in the biological environment, reducing potential harm to human tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843124A_ABST
    Figure CN119843124A_ABST
Patent Text Reader

Abstract

The invention discloses a biomedical magnesium-based composite material as well as a preparation method and application thereof, and belongs to the technical field of biomedical materials. The preparation raw materials of the biomedical magnesium-based composite material comprise nanometer manganese coated micron titanium particles and magnesium-zinc-zirconium alloy powder; the mass of the micron titanium particles accounts for 1%-5% of the mass of the magnesium-zinc-zirconium alloy powder, and the mass of the nano manganese accounts for 1%-2% of the mass of the magnesium-zinc-zirconium alloy powder; the magnesium-zinc-zirconium alloy powder contains 1wt%-6wt% of zinc, 0.5 wt%-1wt% of zirconium and the balance of magnesium; a nano-scale MnZn2 phase is formed in the biomedical magnesium-based composite material, and part of manganese exists in a magnesium alloy matrix formed by magnesium-zinc-zirconium alloy powder in a solid solution form; the magnesium-based composite material contains 5%-15% by volume of nano twin crystals. The magnesium-based composite material has excellent mechanical properties, corrosion resistance and good biocompatibility, and can meet the requirements of clinical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a biomedical magnesium-based composite material and a preparation method and application thereof. Background Art

[0002] Among biological implant materials, ceramic materials are too brittle and pose potential risks under impact loads in the body; polymer materials often show low strength, rigidity and stability; metal materials have good comprehensive mechanical properties and have been widely used in orthopedics, oral repair and cardiovascular treatment. Among them, biological magnesium alloys have good biocompatibility and biosafety, and show great application prospects in implantable medical devices such as bone stents, cardiovascular stents and bone nails.

[0003] Compared with other medical metals (such as stainless steel), the Young's modulus of magnesium alloy is closer to that of natural bone tissue, which helps to reduce the stress shielding effect during bone reconstruction and create a more favorable environment for bone healing and integration with surrounding tissues. Importantly, magnesium alloy can gradually degrade in the body until it is completely absorbed during service, cleverly meeting its clinical needs as a temporary substitute; at the same time, the magnesium ions released by degradation can not only participate in a variety of metabolic reactions in the body, but also play a key role in the activity, proliferation and differentiation of bone cells. The above characteristics have enabled the application of biological magnesium alloys to change the design and function of traditional medical metal implants, bringing new medical effects, and it is hailed as a "revolutionary medical metal material."

[0004] The series of biomedical magnesium alloys currently under development have attracted wide attention due to their excellent comprehensive properties, especially in the application of orthopedic implants and cardiovascular stents (such as cardiovascular stents, bone fixation materials, porous bone repair materials, wound suture materials, etc.), and have made substantial and encouraging research progress. However, the standard electrode potential of magnesium is very low, it is easy to corrode, and it is impossible to form an effective protective oxide film, especially Cl in body fluids. -It will accelerate the corrosion of magnesium alloy. The faster degradation rate causes the implant material to corrode seriously before the body is healed, which reduces the mechanical properties and stability of the material, makes the material fail, and may even completely degrade. At the same time, the rapid corrosion of magnesium alloy is accompanied by a large release of hydrogen, which does not have time to diffuse and absorb and forms bubbles around the implant. Although bubbles can be removed by subcutaneous puncture, the formation of bubbles will affect the physiological function of the tissue around the implant and the recovery treatment of the implant site to a certain extent. In addition, the excessively fast degradation rate will increase the local pH value of the body fluid near the implant, which will have potential harm to the growth of human bones and tissues, for example, causing protein deposition and inflammation in human tissues, or hemolysis and local bone dissolution. It is precisely because of the faster degradation rate of magnesium alloy and the resulting material failure, large-scale concentrated release of hydrogen and increased pH that restrict the application of magnesium alloy in biomedical clinical practice.

[0005] Therefore, using elements such as magnesium, zinc, zirconium, manganese, etc. required by the human body to alloy the matrix, and then regulating the microstructure of magnesium-based composites, improving the mechanical properties of magnesium-based composites and the corrosion rate in biological fluids, is the key to the widespread application of implant materials in the biomedical field.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The object of the present invention is to provide a biomedical magnesium-based composite material and a preparation method and application thereof, so as to solve or improve the above technical problems.

[0008] The present invention can be implemented like this: In a first aspect, the present invention provides a biomedical magnesium-based composite material, wherein the raw materials for preparing the biomedical magnesium-based composite material include nano-manganese-coated micron titanium particles and magnesium-zinc-zirconium alloy powder; In the nano-manganese-coated micron titanium particles, the mass of the micron titanium particles is 1% to 5% of the magnesium-zinc-zirconium alloy powder, and the mass of the nano-manganese is 1% to 2% of the magnesium-zinc-zirconium alloy powder; the magnesium-zinc-zirconium alloy powder contains 1wt% to 6wt% zinc and 0.5wt% to 1wt% zirconium, and the balance is magnesium; Nano-scale MnZn2 phase is formed at the bonding interface between the nano-manganese-coated micron titanium particles and the magnesium alloy matrix formed by the magnesium-zinc-zirconium alloy powder, and part of the manganese in the nano-manganese-coated micron titanium particles exists in the magnesium alloy matrix formed by the magnesium-zinc-zirconium alloy powder in the form of solid solution; the biomedical magnesium-based composite material contains high-density nano-sized twins with a volume fraction of 5% to 15%.

[0009] In an optional embodiment, the biomedical magnesium-based composite material has at least one of the following characteristics: Feature 1: The average particle size of the magnesium-zinc-zirconium alloy powder is 50μm~80μm; Feature 2: The grains in the biomedical magnesium-based composites are mainly in an equiaxed state after recrystallization, with a grain size of 1.0μm~3.0μm and no obvious texture orientation; Feature 3: In the nano-manganese coated micron titanium particles, nano-manganese is uniformly coated on the surface of the micron titanium particles.

[0010] In an optional embodiment, the biomedical magnesium-based composite material further has at least one of the following characteristics: Feature 4: The size of the twins contained in the biomedical magnesium-based composite material is 0.1μm~1μm; Feature 5: The tensile strength of biomedical magnesium-based composite materials is not less than 340MPa; Feature 6: The yield strength of biomedical magnesium-based composite materials is not less than 305MPa; Feature 7: The elastic modulus of biomedical magnesium-based composite materials is 41GPa~43GPa; Feature 8: The corrosion rate of biomedical magnesium-based composite materials is no more than 0.18 mm / a at a pH value of 7.4 to 7.6.

[0011] In a second aspect, the present invention provides a method for preparing a biomedical magnesium-based composite material as described in any of the aforementioned embodiments, comprising the following steps: ball milling nano-manganese-coated micron titanium particles and magnesium-zinc-zirconium alloy powder, followed by spark plasma sintering and hot free forging deformation.

[0012] In an optional embodiment, the preparation of nano-manganese coated micron titanium particles includes: coating nano-manganese powder on the surface of micron titanium particles by radio frequency plasma to obtain nano-manganese coated micron titanium particles; The average particle size of the nano manganese powder is 200nm~500nm, the average particle size of the micron titanium particles is 10μm~20μm, and the coating thickness is 0.1μm~1μm.

[0013] In an optional embodiment, the RF plasma conditions include: a plasma power of 33 kW to 45 kW, a powder feeding rate of 12 g / min to 16 g / min, and an argon carrier gas flow rate of 70 L / min to 90 L / min.

[0014] In an optional embodiment, the ball milling conditions include: a ball-to-material ratio of 20:1 to 30:1, a ball milling time of 1 h to 2 h, and a ball milling speed of 180 rpm to 220 rpm.

[0015] In an optional implementation manner, the temperature of the spark plasma sintering is 500° C. to 520° C., the pressure of the spark plasma sintering is 30 MPa to 40 MPa, the time of the spark plasma sintering is 5 min to 9 min, and air cooling is performed after the spark plasma sintering.

[0016] In an optional embodiment, the temperature of the hot free forging deformation is 300° C. to 350° C., and the rate of the hot free forging deformation is 100 mm / min to 200 mm / min.

[0017] In a third aspect, the present invention provides a medical implant, wherein the raw materials for preparing the medical implant include the biomedical magnesium-based composite material of the aforementioned embodiment.

[0018] The beneficial effects of the present invention include: The biomedical magnesium-based composite material provided by the present invention is prepared from nano-manganese-coated micron titanium particles and magnesium-zinc-zirconium alloy powder in a specific ratio, wherein the nano-manganese particles uniformly coated on the surface of the titanium particles preferentially combine with the zinc element in the magnesium-zinc-zirconium matrix alloy powder at the interface to form a nano-scale MnZn2 phase in situ. The nano-scale MnZn2 phase synergizes with the titanium particles to hinder the movement of the grain boundary, so that the grains of the composite material are significantly refined, and the formation of high-density, small-size twins is promoted. In addition, in addition to a part of the manganese element reacting in situ at the interface to form the MnZn2 phase, a part of the manganese element is solid-dissolved into the magnesium alloy matrix, which plays an orowan strengthening role and significantly improves the mechanical properties of the biomedical magnesium-based composite material.

[0019] At the same time, due to the good corrosion resistance of manganese itself, no severe galvanic corrosion occurs between manganese and the matrix, which can significantly improve the overall corrosion resistance of the composite material.

[0020] The present invention specifically controls the quality of nano-manganese to 1% to 2% of the magnesium-zinc-zirconium alloy powder. The reason is that as the manganese content increases, the corrosion rate of the composite material first decreases significantly. As too many manganese particles are added, the corrosion rate rises, but it is still better than the magnesium alloy without manganese. This is mainly because too much manganese remains at the interface, promoting the formation of large-sized twins. The presence of large-sized twins will reduce the plasticity and ductility of metal materials, and cracks are likely to expand and crack along the twin boundaries, causing the material to be prone to fracture and fatigue damage. In addition, large-sized twins are a kind of defect-like existence, which easily promotes local electrochemical reactions in the material and accelerates the corrosion of the material. The reason may be that the large-sized twin structure makes it easier for the material to form electrochemical inhomogeneities in a corrosive environment, resulting in accelerated local corrosion and serious reduction of the service life of biomedical materials.

[0021] Therefore, selecting an appropriate amount of manganese element to coat micron titanium particles to reinforce magnesium-zinc-zirconium alloy can help improve the mechanical properties of biomedical implant magnesium-based composite materials, improve the appropriate corrosion rate, and significantly improve the service life of implant materials in biological environments. In addition, the biomedical magnesium-based composite material contains high-density nano-sized twins with a volume fraction of 5% to 15%, which is conducive to controlling the degradation rate of biomedical magnesium-based composite materials within an appropriate range.

[0022] The biomedical magnesium-based composite material provided by the invention has high yield strength, tensile strength, suitable elastic modulus and low corrosion rate, and can be used as a biomedical implant. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 This is a SEM image of the nano-manganese-coated micron titanium particles prepared in Example 1; Figure 2 This is a cross-sectional SEM image of the biomedical magnesium-based composite material prepared in Example 1; Figure 3 This is a longitudinal cross-sectional SEM image of the biomedical magnesium-based composite material prepared in Example 1; Figure 4 This is a transmission electron microscope image of high-density, small-sized twins in the biomedical magnesium-based composite material prepared in Example 1; Figure 5 This is a transmission electron microscope image of the nano-scale MnZn2 phase in the biomedical magnesium-based composite material prepared in Example 1; Figure 6 This is a transmission electron microscope image of large-sized twins in the biomedical magnesium-based composite material prepared in Comparative Example 10. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0026] The biomedical magnesium-based composite material provided by the present invention and its preparation method and application are described in detail below.

[0027] The invention provides a biomedical magnesium-based composite material. The raw materials for preparing the biomedical magnesium-based composite material include nano-manganese-coated micron titanium particles and magnesium-zinc-zirconium alloy powder.

[0028] In the above-mentioned nano-manganese-coated micron titanium particles, the mass of the micron titanium particles is 1% to 5% of the magnesium-zinc-zirconium alloy powder, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., and can also be other values ​​within the range of 1% to 5%.

[0029] If the amount of micron titanium particles is too small, it is not conducive to improving the strength of the magnesium-based composite material; if the amount of micron titanium particles is too large, the number of interfaces between the particles and the matrix is ​​too large, which is not conducive to improving the plasticity of the composite material.

[0030] The mass of nano-manganese is 1% to 2% of the magnesium-zinc-zirconium alloy powder, such as 1%, 1.5% or 2%, etc., and can also be other values ​​within the range of 1% to 2%.

[0031] If the amount of nano-manganese is too little, the area of ​​the coated micron titanium particles is small, which is not conducive to the reaction of manganese and zinc at the interface, and the interface bonding cannot be significantly improved; if the amount of nano-manganese is too much, it is easy to form agglomeration at the interface, which is not conducive to uniform coating and dispersion. At the same time, if the manganese content is too much, it is easy to form large-sized MnZn2 phases and large-sized twins at the interface, which is not conducive to grain refinement, mechanical properties and corrosion performance. Improvement. By adjusting the manganese content in the magnesium-based composite material within the above range provided in this application, the grain and twin size can be more accurately refined, and the mechanical properties and degradation rate of the biomedical magnesium-based composite material can be controlled in a large range.

[0032] The magnesium-zinc-zirconium alloy powder contains 1wt% to 6wt% zinc and 0.5wt% to 1wt% zirconium, with the balance being magnesium. The zinc content may be 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or 6wt%, or other values ​​within the range of 1wt% to 6wt%. The zirconium content may be 0.5wt%, 0.8wt% or 1wt%, or other values ​​within the range of 0.5wt% to 1wt%.

[0033] In the biomedical magnesium-based composite material provided by the present invention, nano-manganese-coated micron titanium particles and a magnesium alloy matrix formed by magnesium-zinc-zirconium alloy powder form a nano-scale MnZn2 phase at the bonding interface, and part of the manganese in the nano-manganese-coated micron titanium particles exists in the magnesium alloy matrix formed by magnesium-zinc-zirconium alloy powder in the form of solid solution.

[0034] In addition, in the biomedical magnesium-based composite material provided by the present invention, the magnesium-based composite material contains high-density twins with a volume fraction of 5% to 15% and a size of 0.1 μm to 1 μm. This content of twins is conducive to controlling the degradation rate of the biomedical magnesium-based composite material within a suitable range. It should be noted that the twins in the biomedical magnesium-based composite material refer to the presence of two or more crystals in the biomedical magnesium-based composite material, and their crystal structures are mirror images of each other. The formation of twins is due to the small energy difference in certain directions during the crystallization process, which makes the crystal planes deflect each other at a certain angle to form twin boundaries, thereby forming twins. The nano-sized twin structure can increase the number of grain boundaries, which can serve as a barrier for the corrosive medium to enter the material, thereby slowing down the corrosion process in the biological environment. Under the synergistic effect of nano twins and low-angle grain boundaries, it is easier to form a stable passivation film on the surface of the material, further improving its corrosion resistance. At the same time, the nano twin structure reduces dislocation movement, so that when the material is subjected to external force, the plastic deformation is more uniform, the stress concentration is reduced, and the mechanical properties of the material are improved.

[0035] In some optional embodiments, in the nano-manganese coated micron titanium particles, the nano-manganese is uniformly coated on the surface of the micron titanium particles.

[0036] In some optional embodiments, the average particle size of the magnesium-zinc-zirconium alloy powder may be 50 μm to 80 μm, such as 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm or 80 μm, or other values ​​within the range of 50 μm to 80 μm.

[0037] If the average particle size of the magnesium-zinc-zirconium alloy powder is less than 50 μm, the magnesium alloy powder is relatively active, which is not conducive to ensuring the safety during hot sintering and hot extrusion preparation; if the average particle size of the magnesium-zinc-zirconium alloy powder is greater than 80 μm, the pores between the powders are relatively large, which is not conducive to obtaining a magnesium-based composite material with dense sintering and fine grain size.

[0038] In some optional embodiments, the grains in the biomedical magnesium-based composite material are mainly in an equiaxed state after recrystallization, and the grain size is 1.0μm~3.0μm (such as 1.0μm, 1.5μm, 2.0μm, 2.5μm or 3.0μm, etc.), without obvious texture orientation. In some more typical embodiments, the grain size in the biomedical magnesium-based composite material is 1.5μm~2.1μm, such as 1.5μm, 1.8μm or 2.1μm, etc.

[0039] In some optional embodiments, the tensile strength of the biomedical magnesium-based composite material provided by the present invention is not less than 340 MPa, such as 340 MPa to 360 MPa, such as 342 MPa, 346 MPa or 358 MPa.

[0040] In some optional embodiments, the yield strength of the biomedical magnesium-based composite material provided by the present invention is not less than 305 MPa, such as 305 MPa to 333 MPa, such as 305 MPa, 325 MPa or 333 MPa.

[0041] In some optional embodiments, the elastic modulus of the biomedical magnesium-based composite material provided by the present invention is 41 GPa to 43 GPa, such as 41 GPa, 42 GPa or 43 GPa, etc. The elastic modulus is close to the elastic modulus of human bone, so that it has good biocompatibility and is suitable for use as a medical implant.

[0042] In some optional embodiments, the corrosion rate of the biomedical magnesium-based composite material provided by the present invention under the condition of pH value of 7.4-7.6 is not higher than 0.18 mm / a, such as 0.12 mm / a-0.18 mm / a, such as 0.12 mm / a, 0.15 mm / a or 0.18 mm / a, etc. This corrosion rate is low and is suitable for use as a medical implant.

[0043] That is, the magnesium-based composite material provided by the present invention has higher strength, suitable elastic modulus and lower corrosion rate, and can meet the requirements of clinical application.

[0044] Correspondingly, the present invention also provides a method for preparing the above-mentioned biomedical magnesium-based composite material, comprising the following steps: ball milling nano-manganese-coated micron titanium particles and magnesium-zinc-zirconium alloy powder, followed by spark plasma sintering and hot free forging deformation.

[0045] In some optional embodiments, the preparation of nano-manganese coated micron titanium particles includes: coating nano-manganese powder on the surface of micron titanium particles by radio frequency plasma to obtain nano-manganese coated micron titanium particles.

[0046] The average particle size of the nano manganese powder may be 200 nm to 500 nm, such as 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, or may be other values ​​within the range of 200 nm to 500 nm.

[0047] If the average particle size of the nano-manganese powder is less than 200nm, the specific surface area is large and easy to agglomerate, which is not conducive to uniform coating on the surface of micron titanium particles, and the effect of improving the interface is significantly reduced; if the average particle size of the nano-manganese powder is greater than 500nm, the effect of coating micron titanium is significantly reduced, and the MnZn2 and twin sizes formed by the interface reaction are large, which is not conducive to further refinement of the grain size, and the corrosion resistance will also be significantly reduced.

[0048] The average particle size of the micron titanium particles may be 10 μm to 20 μm, such as 10 μm, 12 μm, 15 μm, 18 μm or 20 μm, etc., or may be other values ​​within the range of 10 μm to 20 μm.

[0049] If the average particle size of the micron titanium particles is greater than 20 μm, the pores between the powders are too large, which is not conducive to the dense sintering of the composite material.

[0050] The coating thickness may be 0.1 μm to 1 μm, such as 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm or 1 μm, etc., or may be other values ​​within the range of 0.1 μm to 1 μm.

[0051] It should be noted that if the nano-manganese powder and the micron-titanium particles are simply mechanically mixed instead of being prepared into the form of manganese-coated titanium, a Ti-Mn alloy will be formed after mechanical ball milling, weakening the solid solution effect of the Mn element; and in the subsequent preparation process, it cannot react at the interface to form a nano-scale MnZn2 phase, the effect of weakening the grain size is greatly reduced, the driving force for the formation of small-size twins is weakened, and the corrosion resistance is reduced accordingly.

[0052] In some optional embodiments, the RF plasma conditions include: a plasma power of 33 kW to 45 kW, a powder feeding rate of 12 g / min to 16 g / min, and an argon carrier gas flow rate of 70 L / min to 90 L / min.

[0053] Among them, the plasma power can be 33kW, 35kW, 38kW, 40kW, 42kW or 45kW, etc., or other values ​​within the range of 33kW~45kW.

[0054] The powder feeding rate may be 12 g / min, 13 g / min, 14 g / min, 15 g / min or 16 g / min, etc., or may be other values ​​within the range of 12 g / min to 16 g / min.

[0055] The argon carrier gas flow rate can be 70 L / min, 75 L / min, 80 L / min, 85 L / min or 90 L / min, etc., or other values ​​within the range of 70 L / min to 90 L / min.

[0056] In some optional embodiments, the ball milling conditions include: a ball-to-material ratio of 20:1 to 30:1, a ball milling time of 1 h to 2 h, and a ball milling speed of 180 rpm to 220 rpm.

[0057] The ball-to-material ratio may be 20:1, 22:1, 25:1, 28:1 or 30:1, or other values ​​within the range of 20:1 to 30:1.

[0058] The ball milling time can be 1 h, 1.5 h or 2 h, etc., or other values ​​within the range of 1 h to 2 h.

[0059] The ball milling speed may be 180 rpm, 190 rpm, 200 rpm, 210 rpm or 220 rpm, etc., or may be other values ​​within the range of 180 rpm to 220 rpm.

[0060] In some optional implementations, the temperature of spark plasma sintering is 500° C. to 520° C., the pressure of spark plasma sintering is 30 MPa to 40 MPa, the time of spark plasma sintering is 0.5 min to 0.9 min, and air cooling is performed after spark plasma sintering.

[0061] The spark plasma sintering temperature may be 500° C., 505° C., 510° C., 515° C. or 520° C., or other values ​​within the range of 500° C. to 520° C.

[0062] If the temperature of spark plasma sintering is higher than 520°C, it is easy to cause oxidation of metallic magnesium, accelerate the growth rate of the crystal, cause the grains to coarsen and grow, and more pores are easily formed inside the metal material, affecting the mechanical properties and corrosion resistance of the implant material.

[0063] The spark plasma sintering time may be 5 min, 6 min, 7 min, 8 min or 9 min, etc., or may be other values ​​within the range of 5 min to 9 min.

[0064] In some optional embodiments, the temperature of the hot free forging deformation is 300° C. to 350° C., and the rate of the hot free forging deformation is 100 mm / min to 200 mm / min.

[0065] Among them, the temperature of hot free forging deformation can be 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C or 350°C, etc., or other values ​​within the range of 300°C~350°C.

[0066] The above hot free forging deformation temperature can obtain a fine equiaxed crystal structure after dynamic recrystallization, and the texture orientation is significantly weakened.

[0067] If the temperature of hot free forging deformation is too low, it is not conducive to the thermoplastic deformation of the composite material, and the work hardening phenomenon is serious; if the temperature of hot free forging deformation is too high, it is easy to cause serious coarsening of the grains, and the oxygen and other oxidizing gases in the magnesium alloy penetrate into the gaps between the grains to form a eutectic of fusible oxides, destroying the connection between the grains, resulting in a sharp decrease in the plasticity of the material.

[0068] The hot free forging deformation rate can be 100 mm / min, 120 mm / min, 150 mm / min, 180 mm / min or 200 mm / min, etc., or other values ​​within the range of 100 mm / min to 200 mm / min.

[0069] It should be noted that the hot free forging deformation process is a favorable stress state of compressive stress, so it has obvious advantages in processing metals with poor machinability. The use of this uniform large plastic deformation method helps to refine the grain size and introduce high-density twins, thereby significantly improving the mechanical properties of composite materials.

[0070] As mentioned above, nano-manganese-uniformly coated micron titanium particles were successfully prepared by using a radio frequency plasma method. The obtained nano-manganese-coated micron titanium particles and magnesium-zinc-zirconia alloy were ball-milled under the above conditions. The manganese element uniformly coated on the surface of the titanium particles can react with the matrix magnesium alloy at the interface to form a fine nano-scale MnZn2 phase in situ. This phase cooperates with the titanium particles to help refine the average grain size of the composite material. At the same time, a portion of the manganese element enters the magnesium alloy matrix in the form of solid solution, promoting the formation of high-density, nano-sized twins, which helps to improve the corrosion resistance of biomedical magnesium-based composite materials and significantly improve the service life of implant materials in biological environments. In addition, the elastic modulus of the biomedical magnesium-based composite material is moderate, which is similar to the elastic modulus of bones, avoiding the occurrence of stress concentration fracture failure of implant materials.

[0071] In addition, the present invention also provides a medical implant, the raw materials for preparing the medical implant include the above-mentioned biomedical magnesium-based composite material.

[0072] Exemplarily, the medical implant may include a cardiovascular stent, a bone fixation material, a porous bone repair material, or a wound suture material.

[0073] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0074] Example 1 This embodiment provides a biomedical magnesium-based composite material, the preparation method of which includes: S1: using radio frequency plasma equipment to coat nano-manganese powder on the surface of micron titanium particles to obtain nano-manganese coated micron titanium particles.

[0075] The average particle size of the nano manganese powder is 200 nm, the average particle size of the micron titanium particles is 10 μm, the coating thickness is 0.5 μm, the plasma power is 40 kW, the powder feeding rate is 14 g / min, and the argon carrier gas flow rate is 80 L / min.

[0076] S2: ball milling the nano-manganese coated micron titanium particles and magnesium-zinc-zirconium alloy powder.

[0077] The mass of the micron titanium particles is 5.0% of the magnesium-zinc-zirconium alloy powder, and the mass of the nano-manganese is 2.0% of the magnesium-zinc-zirconium alloy powder. The magnesium-zinc-zirconium alloy powder contains 4wt% zinc and 0.5wt% zirconium, and the remainder is magnesium, which is recorded as Mg4Zn0.5Zr alloy powder. The average particle size of the magnesium-zinc-zirconium alloy powder is 60μm. The ball-to-material ratio is 25:1, the ball milling speed is 180r / min, and the ball milling time is 1.0h.

[0078] S3: The ball-milled material is subjected to spark plasma sintering and then air-cooled to room temperature.

[0079] The spark plasma sintering temperature is 500° C., the spark plasma sintering pressure is 40 MPa, and the spark plasma sintering time is 5 min.

[0080] S4: The sintered part after spark plasma sintering is subjected to hot free forging deformation to obtain a biomedical magnesium-based composite material.

[0081] The temperature of hot free forging deformation is 350°C, and the rate of hot free forging deformation is 100 mm / min.

[0082] Example 2 This embodiment provides a biomedical magnesium-based composite material, the preparation method of which includes: S1: using radio frequency plasma equipment to coat nano-manganese powder on the surface of micron titanium particles to obtain nano-manganese coated micron titanium particles.

[0083] The average particle size of nano manganese powder is 400nm, the average particle size of micron titanium particles is 15μm, the coating thickness is 0.1μm, the plasma power is 33kW, the powder feeding rate is 12g / min, and the argon carrier gas flow rate is 70L / min.

[0084] S2: ball milling the nano-manganese coated micron titanium particles and magnesium-zinc-zirconium alloy powder.

[0085] Specifically, the mass of the micron titanium particles is 3.0% of the magnesium-zinc-zirconium alloy powder, and the mass of the nano-manganese is 1.5% of the magnesium-zinc-zirconium alloy powder. The magnesium-zinc-zirconium alloy powder contains 3wt% zinc and 0.8wt% zirconium, and the remainder is magnesium, which is recorded as Mg3Zn0.8Zr alloy powder. The average particle size of the magnesium-zinc-zirconium alloy powder is 70μm. The ball-to-material ratio is 20:1, the ball milling speed is 200r / min, and the ball milling time is 2h.

[0086] S3: The ball-milled material is subjected to spark plasma sintering and then air-cooled to room temperature.

[0087] The spark plasma sintering temperature is 510° C., the spark plasma sintering pressure is 30 MPa, and the spark plasma sintering time is 6 min.

[0088] S4: The sintered part after spark plasma sintering is subjected to hot free forging deformation to obtain a biomedical magnesium-based composite material.

[0089] The temperature of hot free forging deformation is 300°C, and the rate of hot free forging deformation is 200 mm / min.

[0090] Example 3 This embodiment provides a biomedical magnesium-based composite material, the preparation method of which includes: S1: using radio frequency plasma equipment to coat nano-manganese powder on the surface of micron titanium particles to obtain nano-manganese coated micron titanium particles.

[0091] The average particle size of the nano manganese powder is 500nm, the average particle size of the micron titanium particles is 20μm, the coating thickness is 1μm, the plasma power is 45kW, the powder feeding rate is 16g / min, and the argon carrier gas flow rate is 90L / min.

[0092] S2: ball milling the nano-manganese coated micron titanium particles and magnesium-zinc-zirconium alloy powder.

[0093] Specifically, the mass of the micron titanium particles is 1.0% of the magnesium-zinc-zirconium alloy powder, and the mass of the nano-manganese is 1.0% of the magnesium-zinc-zirconium alloy powder. The magnesium-zinc-zirconium alloy powder contains 2wt% zinc and 1wt% zirconium, and the remainder is magnesium, which is recorded as Mg2Zn1Zr alloy powder. The average particle size of the magnesium-zinc-zirconium alloy powder is 80μm. The ball-to-material ratio is 30:1, the ball milling speed is 220r / min, and the ball milling time is 1h.

[0094] S3: The ball-milled material is subjected to spark plasma sintering and then air-cooled to room temperature.

[0095] The spark plasma sintering temperature is 520° C., the spark plasma sintering pressure is 35 MPa, and the spark plasma sintering time is 9 minutes.

[0096] S4: The sintered part after spark plasma sintering is subjected to hot free forging deformation to obtain a biomedical magnesium-based composite material.

[0097] The temperature of hot free forging deformation is 325°C, and the rate of hot free forging deformation is 150 mm / min.

[0098] Comparative Example 1 The difference between this comparative example and Example 1 is that in S1, the nano manganese powder and the micron titanium particles are directly mechanically mixed without coating treatment.

[0099] Comparative Example 2 The difference between this comparative example and Example 1 is that in S1, Cu is used instead of Mn.

[0100] Comparative Example 3 The difference between this comparative example and Example 1 is that in S1, the average particle size of the nano-manganese powder is 10 nm.

[0101] Comparative Example 4 The difference between this comparative example and Example 1 is that in S1, the average particle size of the nano manganese powder is 600 nm.

[0102] Comparative Example 5 The difference between this comparative example and Example 1 is that in S1, the average particle size of the micron titanium particles is 5 μm.

[0103] Comparative Example 6 The difference between this comparative example and Example 1 is that in S1, the average particle size of the micron titanium particles is 50 μm.

[0104] Comparative Example 7 The difference between this comparative example and Example 1 is that in S2, the mass of the micron titanium particles is 0.5% of the magnesium-zinc-zirconium alloy powder.

[0105] Comparative Example 8 The difference between this comparative example and Example 1 is that in S2, the mass of the micron titanium particles is 10% of the magnesium-zinc-zirconium alloy powder.

[0106] Comparative Example 9 The difference between this comparative example and Example 1 is that in S2, the mass of nano-manganese is 0.5% of the magnesium-zinc-zirconium alloy powder.

[0107] Comparative Example 10 The difference between this comparative example and Example 1 is that in S2, the mass of nano-manganese is 5% of the magnesium-zinc-zirconium alloy powder.

[0108] Comparative Example 11 The difference between this comparative example and Example 1 is that in S2, the average particle size of the magnesium-zinc-zirconium alloy powder is 20 μm.

[0109] Comparative Example 12 The difference between this comparative example and Example 1 is that in S2, the average particle size of the magnesium-zinc-zirconium alloy powder is 100 μm.

[0110] Comparative Example 13 The difference between this comparative example and Example 1 is that in S4, the temperature of spark plasma sintering is 550°C.

[0111] Comparative Example 14 The difference between this comparative example and Example 1 is that in S5, the temperature of hot free forging deformation is 280°C.

[0112] Comparative Example 15 The difference between this comparative example and Example 1 is that in S5, the temperature of hot free forging deformation is 380°C.

[0113] Test example ① Taking the biomedical magnesium-based composite materials prepared in Example 1 and Comparative Example 10 as examples, the morphology thereof was detected, and the transmission fine structure of the MnZn2 phase and high-density twins formed therein was characterized. The results are as follows: Figures 1 to 6 And as shown in Table 1.

[0114] Depend on Figures 1 to 5 It can be seen that in the biomedical magnesium-based composite material (denoted as Ti@Mn / Mg4Zn0.5Zr) prepared in Example 1, a part of the manganese element forms a fine MnZn2 phase on the grain boundary. The nanoscale rectangular phase synergizes with the nano-titanium particles, which is more conducive to hindering the movement of the grain boundaries. At the same time, a part of the manganese particles dissolved into the magnesium alloy matrix are entangled with dislocations, causing stress concentration, which is conducive to the formation of high-density, small-sized twins, and is beneficial to significantly improve the mechanical properties and biological corrosion resistance rate of the biomedical magnesium-based composite material.

[0115] Among them, Figure 1 It can be seen that the nano-manganese elements are evenly coated on the surface of the micron titanium particles, and the titanium particles, as dispersed carriers, help to reduce the agglomeration of the nano-manganese elements.

[0116] Depend on Figures 2 to 4 It can be seen that in the biomedical magnesium-based composite material, the micron titanium particles are mainly distributed on the grain boundaries, a fine MnZn2 phase is formed on the interface, and many fine manganese phases are precipitated inside the grains.

[0117] Depend on Figure 5It can be seen that: there are high-density, small-sized twins inside the biomedical magnesium-based composite material. The formation of twins will cause a certain amount of deformation, thereby alleviating local stress concentration and coordinating the plastic deformation of the metal. At the same time, the generation of small-sized twins will induce the rotation of the lattice structure to form a new crystal orientation, which is conducive to activating more types of slip systems. Moreover, the interlaced twin boundaries divide the mother crystal into several small grains, inducing the Hall-Petch effect and hindering the movement of dislocations. Dislocations accumulate at the grain boundaries, causing stress concentration, which may provide new nucleation sites for twins or secondary twins. These mechanisms work together to help improve mechanical properties and biological corrosion resistance.

[0118] Depend on Figure 6 It can be seen that the biomedical magnesium-based composite material prepared in Comparative Example 10, due to the excess manganese element, leads to the formation of large-sized twins. The large-sized twins are arranged in parallel and show obvious texture orientation. Large-sized twins are prone to form stress concentration at the grain boundaries when subjected to force, leading to cracks and fractures. Defects in the growth process of large-sized twins will significantly weaken the toughness of the material, making the internal structure of the material uneven and affecting the overall mechanical properties of the material. The grain boundary stability of large-sized twins is poor, which easily leads to corrosion at the grain boundaries occurring preferentially. The grain boundary is the weak link in the material. The grain boundary area of ​​large-sized twins is large, which increases the chances of penetration and attack by corrosive media, thereby accelerating the biological corrosion process.

[0119] ②. The biomedical magnesium-based composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 15 were tested for mechanical properties and biological corrosion resistance. The results are shown in Table 1.

[0120] Among them, the tensile test is to apply tensile force to the material sample under standard room temperature conditions until it breaks, measure its stress-strain relationship, and test it according to the "GB / T 228.1-2010" standard to calculate the yield strength and tensile strength; the elastic modulus is calculated by the ratio of stress to strain within the elastic deformation range of the tensile test; the biological corrosion resistance is tested in an environment that simulates the human body (pH value is 7.4~7.6) according to the "YY / T 1434-2016" standard.

[0121] Table 1 Test results

[0122] It can be seen from Table 1 that the biomedical magnesium-based composite material prepared by the method provided by the present invention has higher yield strength, tensile strength, suitable elastic modulus and more suitable corrosion rate.

[0123] In summary, the biomedical magnesium-based composite material provided by the present invention is a biomedical magnesium-based composite material with a high-density twin structure and controllable degradation. Among them, the titanium particles help to improve the strength and plasticity of the magnesium matrix. At the same time, a part of the manganese element on the surface of the titanium particles can react with the matrix to form a fine MnZn2 phase at the interface, which helps to refine the grains; another part of the manganese element solid-dissolves into the magnesium alloy matrix, promotes the formation of high-density nano-scale twins, and improves the overall mechanical properties and biological corrosion resistance of the alloy. The biomedical magnesium-based composite material provided by the present invention has high yield strength, tensile strength, suitable elastic modulus and more suitable biological corrosion resistance rate, and can be used as a medical implant.

[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A biomedical magnesium-based composite material, characterized in that: The raw materials for preparing the biomedical magnesium-based composite material include nano-manganese-coated micron titanium particles and magnesium-zinc-zirconium alloy powder; In the nano-manganese-coated micron titanium particles, the mass of the micron titanium particles is 1% to 5% of the magnesium-zinc-zirconium alloy powder, and the mass of the nano-manganese is 1% to 2% of the magnesium-zinc-zirconium alloy powder; the magnesium-zinc-zirconium alloy powder contains 1wt% to 6wt% zinc and 0.5wt% to 1wt% zirconium, with the remainder being magnesium; The nano-manganese-coated micron titanium particles and the magnesium alloy matrix formed by the magnesium-zinc-zirconium alloy powder form a nano-scale MnZn2 phase at the bonding interface, and part of the manganese in the nano-manganese-coated micron titanium particles exists in the magnesium alloy matrix formed by the magnesium-zinc-zirconium alloy powder in the form of solid solution; the biomedical magnesium-based composite material contains high-density nano-sized twins with a volume fraction of 5% to 15%.

2. The biomedical magnesium-based composite material according to claim 1, characterized in that: The biomedical magnesium-based composite material has at least one of the following characteristics: Feature 1: The average particle size of the magnesium-zinc-zirconium alloy powder is 50 μm to 80 μm; Feature 2: The grains in the biomedical magnesium-based composite material are mainly in an equiaxed state after recrystallization, with a grain size of 1.0 μm to 3.0 μm and no obvious texture orientation; Feature 3: In the nano-manganese coated micron titanium particles, nano-manganese is uniformly coated on the surface of the micron titanium particles.

3. The biomedical magnesium-based composite material according to claim 2, characterized in that: The biomedical magnesium-based composite material also has at least one of the following characteristics: Feature 4: The size of the twin crystals contained in the biomedical magnesium-based composite material is 0.1 μm to 1 μm; Feature 5: The tensile strength of the biomedical magnesium-based composite material is not less than 340 MPa; Feature 6: The yield strength of the biomedical magnesium-based composite material is not less than 305 MPa; Feature 7: The elastic modulus of the biomedical magnesium-based composite material is 41 GPa to 43 GPa; Feature 8: The corrosion rate of the biomedical magnesium-based composite material is no more than 0.18 mm / a under a pH value of 7.4 to 7.

6.

4. A method for preparing a biomedical magnesium-based composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Nano-manganese-coated micronized titanium particles were ball-milled with magnesium-zinc-zirconium alloy powder, followed by spark plasma sintering and hot free forging deformation.

5. The preparation method according to claim 4, characterized in that: The preparation of the nano-manganese coated micron titanium particles comprises: coating the nano-manganese powder on the surface of the micron titanium particles by radio frequency plasma to obtain the nano-manganese coated micron titanium particles; The average particle size of the nano manganese powder is 200nm-500nm, the average particle size of the micron titanium particles is 10μm-20μm, and the coating thickness is 0.1μm-1μm.

6. The preparation method according to claim 5, characterized in that: The RF plasma conditions include: plasma power of 33 kW to 45 kW, powder feeding rate of 12 g / min to 16 g / min, and argon carrier gas flow rate of 70 L / min to 90 L / min.

7. The preparation method according to claim 4, characterized in that: The ball milling conditions include: a ball-to-material ratio of 20:1 to 30:1, a ball milling time of 1 h to 2 h, and a ball milling speed of 180 rpm to 220 rpm.

8. The preparation method according to claim 4, characterized in that: The temperature of spark plasma sintering is 500°C~520°C, the pressure of spark plasma sintering is 30MPa~40MPa, the time of spark plasma sintering is 5min~9min, and air cooling is performed after spark plasma sintering.

9. The preparation method according to claim 4, characterized in that: The temperature of hot free forging deformation is 300℃~350℃, and the rate of hot free forging deformation is 100mm / min~200mm / min‌.

10. A medical implant, characterized in that: The raw material for preparing the medical implant comprises the biomedical magnesium-based composite material according to claim 1.

Citation Information

Patent Citations

  • Mg17Al12 phase reinforced magnesium-based composite material and preparation method thereof

    CN118516594A

  • Method of producing a medical implant adopting additive manufacturing

    US20240173775A1

Cited By

  • High-modulus magnesium-based composite material as well as preparation method and application thereof

    CN120683402A

  • High modulus magnesium-based composite material and its preparation method and application

    CN120683402B